Prenatal Identification and Molecular Characterization of Two Simultaneous De Novo Interstitial Duplications of Chromosomal Regions 7p22.1p21.1 and 15q24.1 - Sabrina C. Burn; Kali Swift; Maria Palmquist (Case Reports in Genetics)
The occurrence of simultaneous de novo chromosomal aberrations is extremely rare. Here, we describe two, previously unreported, simultaneous de novo interstitial duplications of chromosomes 7p and 15q. Amniocentesis was completed for a healthy gravida 4 para 3 woman due to her advanced maternal age and concurrent ultrasound findings of partial vermian agenesis, choroid-plexus cysts, and hypoplastic nasal bone. Cytogenetic analysis of cultured amniocytes by conventional chromosome analysis, comparative genomic hybridization, and fluorescence in situ hybridization revealed two interstitial duplications of the chromosomal regions 7p22.1p21.1 and 15q24.1, leading to partial trisomy of 7p and 15q and karyotype 46,XY,dup(7)(p22.1-p21.1),dup (15)(q24.1). Parental chromosomal analysis did not identify any heritable changes, suggesting both mutations were de novo in nature. Postnatal examination of the neonate was significant for low set ears, thick helices, flat nasal bridge, ankyloglossia, and aberrant head shape and size concerning for craniosynostosis. Postnatal MRI was consistent with Dandy-Walker variant showing hypogenesis of the inferior cerebellar vermis. To our knowledge, there are no prenatal or postnatal reports of comparable duplications involving these two regions simultaneously. Continued observation of the neonate may reveal further phenotypic consequences of these two simultaneous de novo interstitial duplications.